2011
DOI: 10.1080/09583157.2011.622837
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intraguild competitors on reproductive decisions by two predatory Heteroptera,Orius insidiosus(Anthocoridae) andNabis americoferus(Nabidae)

Abstract: The relationship between the oviposition site preferences of predators in the face of intraguild competitors has received little attention, but it likely shapes the reproductive ecology of predatory species. In this study, oviposition intensity and the within-plant distribution of Orius insidiosus (Heteroptera: Anthocoridae) and Nabis americoferus (Heteroptera: Nabidae) eggs on Phaseolus vulgaris plants was studied when the two species were present independently or in combination. Both predators laid more eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This could explain the location of individuals within the plant. In the absence of other predatory species, the females lay eggs mostly into the leaf petioles spread out equally over the height of the plant [104]. Moreover, Nabis adults prefer to sit on the top or slightly lower in the plant canopy, while immature individuals are found lower down in the plant [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the location of individuals within the plant. In the absence of other predatory species, the females lay eggs mostly into the leaf petioles spread out equally over the height of the plant [104]. Moreover, Nabis adults prefer to sit on the top or slightly lower in the plant canopy, while immature individuals are found lower down in the plant [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Canada, the common damsel bug, Nabis americoferus (Carayon) (Hemiptera: Nabidae), and the minute pirate bug, Orius insidiosus (Say) (Hemiptera: Anthocoridae), have been regularly found preying on TPB (F. Dumont, personal observation). Moreover, Pumariño et al (2011) reported that females of both predators laid more eggs in the presence of their competitor than in the presence of conspecifics [18]. Therefore, releasing both predators in a biological control program may increase the numerical reproductive response and consequently the overall impact on the TPB.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, releasing both predators in a biological control program may increase the numerical reproductive response and consequently the overall impact on the TPB. The same authors suggested that the simultaneous use of an ambush predator, such as N. americoferus, and an active-searching predator, such as O. insidiosus, may generate a facilitation effect [18]. Yet, the action of the active-searching predator would increase the focal prey movement and then increase the encounter opportunity with the ambush predator [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because juveniles and eggs are usually more vulnerable to predation than adults, IG‐prey mothers are expected to select oviposition sites with lower risk of IG predation to increase the survival of their offspring (Almohamad et al, 2010; Choh et al, 2010; van der Hammen et al, 2010; Walzer & Schausberger, 2011). However, IG predators may have a similar preference for oviposition sites as IG prey (Pumariño et al, 2011; Huang & Pike, 2012; Choh et al, 2015; Saitoh & Choh, 2018a). Our recent study showed that IG‐prey mothers protected their eggs against IG predators sharing the same oviposition sites (Saitoh & Choh, 2018a).…”
Section: Introductionmentioning
confidence: 99%